The Comparison of Hand Sewn and Stapled Anastomoses - Hussain, Tanweer; Jabbar, Abdul; Ahmed, Naveed; Shah, Naqeeb; Zulfiqar, Mujahid; ., Anita (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare hand-sewn and stapled sutures and the influence of intestinal excision on postoperative complications.Study Design: Retrospective comparative study.Place and Duration of Study: General Surgery Department of CMH Peshawar, from Jan 2020 to Jan 2021.Methodology: Once receiving consent, all individuals hospitalized in the medical facility for ileostomy closure were included in our investigation. In a questionnaire, postoperative complications were documented.Result: This study involved a total of 60 subjects. Individuals were scheduled for surgery after receiving clearances and a loopogram distally. Thirty patients had their wounds hand-sewn shut, while 30 others had their wounds stapled shut. The mean operating time for the hand-sewn method was 2.46 ± 0.29 hours, compared to 1.86 ± 0.17 hours mean for the stapled method. In both categories, the anastomotic leak was comparable. Thirty patients in the hand-sewn group took a mean of 2.42 ± 0.25 days to return bowel sounds after surgery, whereas it took 1.83 ± 0.20 days to return bowel sounds.Conclusion: The stapler method greatly decreases the duration of surgery, promotes rapid recovery, and has a lower fatality rate. Stapling is a simple procedure that can be performed in inaccessible locations, such as a low colorectal anastomosis. In elective gastrointestinal procedures, stapler anastomosis can be utilized safely and successfully.